Thin Capitalization Determinants in Manufacturing Companies in Indonesia - Septian Adi Hananto; Nurmadi Harsa Sumarta; Edy Supriyono (Universitas Muhammadiyah Surakarta, 2021)
This study aims to analyze the determinants of thin capitalization practices on manufacturing companies in Indonesia. Moreover, this study focuses on the manufacturing sector which ranks as the second largest recipient of foreign debt. The population of this study consisted of all manufacturing companies which had listed on the Indonesia Stock Exchange from 2016 to 2019. Furthermore, the purposive sampling technique was used as a sampling technique and it was obtained 308 samples. The hypothesis analysis technique in this study used the Ordinary Least Square (OLS) method. The results show that tax haven utilization and significant foreign ownership has a positive effect on the practice of thin capitalization. Meanwhile, foreign directors has negative effect on the practice of thin capitalization. However, this study cannot prove the effect of multinationality on the practice of thin capitalization.Keywords: thin capitalization, multinationality, tax haven utilization, significant foreign ownership, foreign directors.